La investigación en ciencias de la información y la documentación: escenarios y perspectivas (2023)
ABSTRACT: A general reflection on research in the field of information sciences is presented, but not without first having an approach to the different views and conceptions that are assumed as information sciences, and then pointing out some considerations about research in this field. area of knowledge, which is complemented with some research experiences in information science, to culminate with some conclusions in this regard.